2016
DOI: 10.1002/mar.20895
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Relationships in Professional Services and the Moderating Role of Relationship Age

Abstract: Empathy has been identified as a key success factor for employees who interact with customers. Despite its overall relevance, only a few studies have acknowledged its multidimensional nature. Knowledge remains scarce about the relative impact of cognitive and affective empathy on relational outcomes. In addition, few pieces of research have explicitly acknowledged empathy as theorized within stage‐models focusing on the communication of empathy. The authors conceptualize empathy as a multidimensional construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 90 publications
(207 reference statements)
0
26
0
Order By: Relevance
“…Moreover, cognitive empathy increases the quality of the relationship (assessed in terms of trust, commitment, reciprocity and exchange efficiency) between business solution customers and their project manager or consultant (Prior, 2016). Similarly, WeiBhaar and Huber (2016) show that client perceptions of consulting agents’ empathy contributed to their trustworthiness, (especially in younger relationships) and identified a positive direct link between agents’ empathy (perspective taking) and their objective sales performance.…”
Section: Beneficiaries Of Empathymentioning
confidence: 82%
“…Moreover, cognitive empathy increases the quality of the relationship (assessed in terms of trust, commitment, reciprocity and exchange efficiency) between business solution customers and their project manager or consultant (Prior, 2016). Similarly, WeiBhaar and Huber (2016) show that client perceptions of consulting agents’ empathy contributed to their trustworthiness, (especially in younger relationships) and identified a positive direct link between agents’ empathy (perspective taking) and their objective sales performance.…”
Section: Beneficiaries Of Empathymentioning
confidence: 82%
“…Over time, customers become more knowledgeable and self‐confident about any service offering and about the service provider (Kalwani & Nayarandas, ; Raimondo, “Nino” Miceli, & Costabile, ), which changes the relative importance of different relational constructs and their influences on outcome variables (Weißhaar & Huber, ). Thus, customers gain confidence (Verhoef, Franses, & Hoekstra, ) based on the benefits received from services with a clear understanding of the offerings and it increases the chance of their satisfaction with the service provider over time.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Wieseke et al (2012) found that "Feeling altruistic" or experiencing customer empathy, defined as customer's apprehension of and reaction to an employee's thoughts, feelings, and intentions during a service interaction, can act as a qualifier of social interactions, nurturing alignment of feelings and thoughts and creating smooth, harmonious interactions. In service research, empirical studies on empathy in employee-customer interactions are scarce (Weißhaar and Huber, 2016) with the majority of prior research studying the impact of employee empathy on customers (e.g. Zeithaml et al,1996).…”
Section: --------------------------------------mentioning
confidence: 99%